Dakwah Islam: Bil Mau'idzah Hasanah dan Meningkatkan Taraf Berfikir Masyarakat - Mujahid, Kasori; Solikhah, Hanik Rahmawati; Efendi, Asmira; Mujahidah, Anny Izzatul (TSAQOFAH, 2025)
Da'wah is part of carrying out Allah's commands, amar ma'ruf nahi munkar. People who preach are usually called da'i or preachers, and in various regions have certain titles such as ustadz, Kyai, musyrif, Gus and so on. One of the pros and cons of carrying out da'wah activities is the use of certain sentences which are considered harsh by some groups. This article will explain the background of the obligation of da'wah for a Muslim, how a Muslim carries out da'wah, namely bil mau'idzah hasanah, the aim of da'wah, namely increasing the level of people's thinking, and recommendations for those who actively carry out da'wah. This article was written using a literature review method sourced from news, books and journals.